Removal, Pre-concentration And Determination Of Selected Pharmaceuticals From Environmental Water Samples - Mohammad, Rania Edrees Adam (2022)
Pharmaceuticals are emerging contaminants that have been widely used in various applications, including human and veterinary medicine, as well as agricultural activities. The pharmaceutical analysis relies on accurate quantification of target pharmaceuticals from a complex matrix, yet this remains a difficult task due to their low concentrations. Therefore, this research demonstrated the use of different sample preparation methods for the determination of selected pharmaceuticals in water samples. A microextraction technique based on vortex-assisted liquid-liquid microextraction with back extraction (VALLME-BE) was developed for the determination of nonsteroidal anti-inflammatory drugs (NSAIDs) namely, ketoprofen, naproxen, diclofenac, and ibuprofen. The procedure was carried out by adding 225 μL of butyl acetate into 10 mL spiked working standard for VALLME procedure, followed by the back-extraction into sodium hydroxide prior to high performance liquid chromatography-UV-Vis (HPLC-UV-Vis) analysis. Under optimum conditions, the proposed technique provided good linearity (R2 ≥ 0.9809), repeatability (%RSD; 3.4 – 16.1), and excellent the limits of detection (LOD) and limit of quantification (LOQ) values (ketoprofen (0.134 and 0.407 μg L-1), naproxen (0.015 and 0.047 μg L-1), diclofenac (0.03 and 0.091 μg L-1) and ibuprofen (0.05 and 0.152 μg L-1) were obtained. On the other hand, graphene oxide (GO), graphene oxide magnetite (GO@Fe3O4), and graphene oxide magnetite-deep eutectic solvent ferrofluid (GO@Fe3O4-DES FF) adsorbents were successfully synthesized and characterized